Outdoor physical activity, compliance with the physical activity, screen time, and sleep duration recommendations, and excess weight among adolescents. (4th December 2019) - Sampasa‐Kanyinga, Hugues; Colman, Ian; Hamilton, Hayley A.; Chaput, Jean‐Philippe
Summary: Background: Spending time outdoor has been identified as an important way to achieve the physical activity required for maintaining and improving health and to lower sedentary time among young children. However, evidence of such relationships in adolescents is particularly limited. This study investigated the relationships between frequency of outdoor physical activity after school, compliance with the physical activity, screen time, and sleep duration recommendations, and overweight/obesity among adolescents. Methods: A total of 10 028 middle and high school students (mean age of 15.2 y) self‐reported the number of weekdays they spent physically active outdoors after school. Physical activity, screen time, sleep duration, height, and weight were self‐reported. Logistic regression models for the total sample and stratified by sex were adjusted for important covariates. Results: Overall, there was a positive gradient between the number of weekdays spent physically active outdoor after school and compliance with the physical activity (more than or equal to 60 min/day at moderate‐to‐vigorous intensity) and screen time (less than or equal to 2 h/day) recommendations while a negative gradient with overweight/obesity was observed. Significant sex differences were observed in the associations of outdoor physical activity after school with adherence to the sleep duration and physical activity recommendations. For example, outdoor physical activity after school on all 5 days was associated with greater odds of compliance with the sleep duration recommendation among males (OR = 1.53; 95% CI, 1.01‐2.31), but not females (OR = 0.92; 95% CI, 0.65‐1.30). Conclusions: Results suggest that outdoor physical activity after school could be a behavioural target to increase compliance with the physical activity and screen time recommendations and to possibly tackle excess weight among adolescents.